Treating the Orthopaedic Trauma Knowledge Gap: Quantification of Orthopaedic Resident Knowledge Gaps and Validation of a Multimodal Course to Address the Deficiencies. Issue 1 (January 2020) - Graves, Matt L.; Paryavi, Ebrahim; Hung, Leroy; Reilly, Mark C.; Guy, Pierre; O'Toole, Robert V.
Abstract : Objectives: To determine whether knowledge-based deficiencies are adequately addressed at the AO North America Basic Principles of Fracture Management course. Design: Pretest, posttest. Setting: Eighteen national trauma courses. Participants: Two thousand one hundred forty-nine learners. Intervention: Pre- and postcourse 20-item tests of basic fracture knowledge, including 14 trauma topics. Main Outcome Measures: Deficiencies were defined as <60% correct answers on the precourse test. Postcourse knowledge gaps were defined as <75% correct responses. Results: Deficiencies were noted in 7 of the 14 topics on the precourse test. All topics with deficiencies on the precourse test were shown to have statistically significant improvement in postcourse test scores. All topics without deficiencies were shown to have statistically significant improvement in postcourse test scores. The average overall precourse test score was 63% (95% confidence interval, 61%–65%), and the average overall postcourse test score was 81% (95% confidence interval, 79%–83%). The pretest to posttest difference was statistically significant ( P < 0.05). The control questions, covering material that was not discussed in the course, did not have statistically significant improvement in scores. Conclusions: Residents are entering residency programs with limited knowledge of fracture care, and significant gaps remain at the junior level at the time of course participation, suggesting that supplemental fracture courses play an important role in resident education. Validation of short-term learning is possible through a pretest and posttest technique, and it can guide design changes, as opposed to relying on satisfaction surveys alone. Abstract : Supplemental Digital Content is Available in the Text.